POTENSI PEMANFAATAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DAN BERBAGAI MEDIA TANAM TERHADAP POPULASI MIKROBA TANAH SERTA PERTUMBUHAN DAN PRODUKSI KENTANG - Christy Nur Cahyani; Yulia Nuraini; Al Gamal Pratomo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
The availability of high quality potato seeds in Indonesia is only 7.4% including imports. Improvement of soil fertility is done with PGPR and various growing media, so that soil quality increases and can increase potato productivity. This research used a split plot design with twelve treatments with three replicates. Treatments tested were P0M1 (without PGPR + Husk Charcoal : Cocopeat (1:1)), P1M1 (10 ml/l PGPR + Husk Charcoal : Cocopeat (1:1)), P2M1 (20 mL L-1 PGPR + Husk Charcoal : Coco peat (1:1)), P0M2 (without PGPR + Soil : Husk Charcoal (1:1)), P1M2 (10 mL L-1 PGPR + Soil : Husk Charcoal (1:1)), P2M2 (20 mL L-1 PGPR + Soil : Husk Charcoal (1:1)), P0M3 (without PGPR + Soil : Husk Charcoal : Cocopeat (1:1:1)), P1M3 (10 mL L-1 PGPR + Soil : Husk Charcoal : Cocopeat (1:1:1)), P2M3 (20 mL L-1 PGPR + Soil : Husk Charcoal : Cocopeat (1:1:1)), P0M4 (without PGPR + Tanah), P1M4 (10 mL L-1 PGPR + Soil), P2M4 (20 mL L-1 PGPR + Soil). PGPR and growing media yielded an interaction with total N-l in P2M2 treatment, with the highest value of 1,02%,. The highest total P was in the P2M2 treatment (0,35%). Nitrogen fixing bacteria were observed in P2M2 treatment with the highest value of 77,25 x 105 cfu mL-1. Phosphate solubilizing bacteria were observed in P2M2 treatment with the highest value of 45 x 105 cfu mL-1. Plant height and dry weight of plants in P2M2 with the highest values of 12,99 cm and 3,61 gram, respectively. The highest yield of potato (20 tubers plant-1) was in the P2M2 treatment.